Transient compartment-like syndrome and normokalaemic periodic paralysis due to a Cav1.1 mutation - Fan, Chunxiang; Lehmann-Horn, Frank; Weber, Marc-André; Bednarz, Marcin; Groome, James R.; Jonsson, Malin K. B.; Jurkat-Rott, Karin (Brain, 2013)
We studied a two-generation family presenting with conditions that included progressive permanent weakness, myopathic myopathy, exercise-induced contracture before normokalaemic periodic paralysis or, if localized to the tibial anterior muscle group, transient compartment-like syndrome (painful acute oedema with neuronal compression and drop foot). 23Na and 1H magnetic resonance imaging displayed myoplasmic sodium overload, and oedema. We identified a novel familial Cav1.1 calcium channel mutation, R1242G, localized to the third positive charge of the domain IV voltage sensor. Functional expression of R1242G in the muscular dysgenesis mouse cell line GLT revealed a 28% reduced central pore inward current and a −20 mV shift of the steady-state inactivation curve. Both changes may be at least partially explained by an outward omega (gating pore) current at positive potentials. Moreover, this outward omega current of 27.5 nS/nF may cause the reduction of the overshoot by 13 mV and slowing of the upstroke of action potentials by 36% that are associated with muscle hypoexcitability (permanent weakness and myopathic myopathy). In addition to the outward omega current, we identified an inward omega pore current of 95 nS/nF at negative membrane potentials after long depolarizing pulses that shifts the R1242G residue above the omega pore constriction. A simulation reveals that the inward current might depolarize the fibre sufficiently to trigger calcium release in the absence of an action potential and therefore cause an electrically silent depolarization-induced muscle contracture. Additionally, evidence of the inward current can be found in 23Na magnetic resonance imaging-detected sodium accumulation and 1H magnetic resonance imaging-detected oedema. We hypothesize that the episodes are normokalaemic because of depolarization-induced compensatory outward potassium flux through both delayed rectifiers and omega pore. We conclude that the position of the R1242G residue before elicitation of the omega current is decisive for its conductance: if the residue is located below the gating pore as in the resting state then outward currents are observed; if the residue is above the gating pore because of depolarization, as in the inactivated state, then inward currents are observed. This study shows for the first time that functional characterization of omega pore currents is possible using a cultured cell line expressing mutant Cav1.1 channels. Likewise, it is the first calcium channel mutation for complicated normokalaemic periodic paralysis.